Knowledge, Behaviors, and Participation in Surveillance, Prevention, and Control of Coronavirus Disease 2019 (COVID-19) in Thai-Myanmar Border Communities: A Case Study - Rattanung, Amornrat; Inchon, Pamornsri; Kanthawee, Phitsanuruk; Saleeon, Thanusin (Health Science Clinical Research, 2024)
Objective: This study aims to compare the levels of knowledge, practices, and participation surveillance, prevention, and control of Coronavirus Disease 2019 (COVID-19) between the Thailand-Myanmar border communities in Mae Sai, Chiang Rai province, and Mae Sot, Tak province. Method: This study employed a cross-sectional descriptive research design with a sample of 400 participants. The sample comprised household representatives aged 18 years and above residing in Thai-Myanmar border communities: 200 from Mae Sai District, Chiang Rai Province, and 200 from Mae Sot District, Tak Province. Participants were selected using area-based stratified random sampling proportional to the population size, focusing on sub-districts adjacent to the Thai-Myanmar border. The research instrument was a questionnaire assessing knowledge, practices, and participation in surveil lance, prevention, and control of Coronavirus Disease 2019 (COVID-19) in Thai-Myanmar bordercommunities. Data analysis involved descriptive statistics to characterize demographic features, chi-square test, Fisher’s exact test, and independent t-test for comparative analysis between the two sample groups from different areas. Results: The majority of participants in both areas demonstrated a high level of knowledge about Coronavirus Disease 2019 (COVID-19), moderate level of preventive practices, and high community participation. Comparison of mean scores between the two areas revealed a statistically significant difference in participation in surveillance, prevention, and control of COVID-19 in the community (p=0.018) at the 0.05 significance level. Furthermore, demographic characteristics including ethnicity (p<.001), occupation (p=.007), income (p<.001), healthcare coverage (p<.001), duration of community residence (p=.005), and community role (p<.001) showed statistically significant differences between the two sample groups at the .05 significance level. Conclusions: Although participation in surveillance, prevention, and control of Coronavirus Disease 2019 (COVID-19) varied between communities, the majority of participants in both areas demonstrated comparable levels of knowledge and preventive practices. To ensure sustainable community participation in disease surveillance and prevention, relevant agencies should foster cooperation between communities, officials, and technology. This approach aims to empower communities and develop innovations leading to resilient communities prepared to handle future emergencies.